2016
DOI: 10.4236/gep.2016.410003
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Study on a Coastal River of Bangladesh with Reference to Irrigation Water Quality Assessment: A Case Study on Shailmari River, Khulna

Abstract: Water quality is the critical environmental determinant that influences the agricultural production and therefore, the economy that solely depends on its agricultural productions. Batiaghata Upazilla is one of the major crop productive areas of Khulna region and the agricultural production here largely depends on the natural water of the Shailmari River system around it. The present study was conducted to assess the suitability of this coastal river water for irrigational use. 66 water samples were collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Thus, these irrigation waters fall into the category of "water of excellent quality, with low risk of alkalinization". These SAR results for the N'Zi River corroborate those obtained by [28]. In addition, by associating the EC with the SAR, the waters of the N'Zi River are divided into two classes: C1S1 and C2S1 corresponding respectively to water of low and medium salinity.…”
Section: Water Suitability Of the N'zi River For Irrigationsupporting
confidence: 85%
“…Thus, these irrigation waters fall into the category of "water of excellent quality, with low risk of alkalinization". These SAR results for the N'Zi River corroborate those obtained by [28]. In addition, by associating the EC with the SAR, the waters of the N'Zi River are divided into two classes: C1S1 and C2S1 corresponding respectively to water of low and medium salinity.…”
Section: Water Suitability Of the N'zi River For Irrigationsupporting
confidence: 85%
“…Hence, the evaluation of its quality across time and location is critical to use the available water resources in an efficient manner. Abel et al (2011), Reddy (2013) and Islam et al (2016) reported that the variability of water quality can pose management challenges in irrigated fields. Thus gathering reliable information on trends of water quality is essential to design appropriate farm management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Thus gathering reliable information on trends of water quality is essential to design appropriate farm management practices. Tessema et al (2014), Abay et al (2016), Islam et al (2016), Nag and Suchetana (2016) and Husien et al (2017) suggested that knowledge on irrigation water quality will help a lot during the development of strategies for farm management practices. Some works on irrigation water quality evaluation were done in the present study area (Mesfin, 2001;Halcrow, 2008;Pascual-Ferrer et al, 2014;Abay et al, 2016;Hadera, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, anthropogenic factors, geological structure and mineralogy of both watersheds and aquifers play a substantial role in controlling the ground water quality (Drever, 1988;Apello & Postma, 2005;Bahar & Reza, 2010). Being an agro based country, Bangladesh possesses 5,049,785 ha agro-arable land which depends on adequate water supply from both groundwater (80.60%) and surface water (19.40%) of usable quality (Shahid et al, 2006;Hasan et al, 2007;Vyas and Jethoo, 2015;Islam et al, 2016). Usually, ground water is a critical concern in coastal Bangladesh as the people in this region are highly reliant on it for sustaining their livelihoods (Hasan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, befitting ground water sources can provide guarantee for the safe water both for domestic uses and irrigation practices. Studies on the surface water quality of Shailmari River System of this area has been already done, but information on ground water is unrevealed yet (Islam et al, 2016). Hence, a detailed investigation of shallow and deep tubewells along the bank of Shailmari River connected with Rupsha-Kazibacha River system could be a very realistic study to assess the quality of groundwater through hydro-chemical investigation and water quality indexing.…”
Section: Introductionmentioning
confidence: 99%